Development and Evaluation of Motion-activated System for Improved Chest Drainage: Bench, In Vivo Results, and Pilot Clinical Use of Technology. (October 2020) - Karimov, Jamshid H.; Dessoffy, Raymond; Fukamachi, Kiyotaka; Okano, Shinji; Idzior, Laura; Lobosky, Mark; Horvath, David
Objective . The aim of this study was to evaluate a motion-activated system (MAS) that applies motion-activated energy (vibration) to prevent chest tube clogging and maintain tube patency. We performed chest tube blood flow analysis in vitro, studied MAS effects on intraluminal clot deposition in vivo, and conducted a pilot clinical test. Background . Chest tube clogging is known to adversely contribute to postoperative cardiac surgery outcomes. Methods . The MAS was tested in vitro with a blood-filled chest tube model for device acceleration and performance. In vivo acute hemothorax studies (n = 5) were performed in healthy pigs (48.0 ± 2 kg) to evaluate the drainage in MAS versus control (no device) groups. Using a high-speed camera (FASTCAM Mini AX200, 100 mm Zeiss lens) in an additional animal study (n = 1), intraluminal whole-blood activation imaging of the chest tube (32 Fr) was made. The pilot clinical study (n = 12) consisted of up to a 30 minutes device tolerance test. Results . In vitro MAS testing suggested optimal device performance. The 2-hour in vivo evaluation showed a longer incremental drainage in the MAS group versus control. The total drainage in the MAS group was significantly higher than that in the control group (379 ± 144 mL vs 143 ± 40 mL; P = .0097), indicating tube patency. The high-speed camera images showed a characteristic intraluminal blood "swirling" pattern. Clinical data showed no discomfort with the MAS use (pleural = 4; mediastinal = 8). Conclusions . The MAS showed optimal performance at bench and better drainage profile in vivo. The clinical trial showed patients' tolerance to the MAS and device safety.